Asuhan Kebidanan Komprehensif Dengan Kehamilan Normal Di Puskesmas Bontonyeleng Tahun 2023 - Nurhalisa, Nurhalisa; Nurlaily, Andi; Asmirati, Asmirati; Fajriani, A. Tenri; Risnawati, Risnawati (Universitas Sumatera Barat, 2023)
Pregnancy, childbirth, and the postpartum period are normal for a mother. However, it may turn out to be abnormal because of several complications that cause MMR and IMR such as bleeding, high blood pressure, or preeclampsia, postpartum infection, lack of routine maternal visits during pregnancy and in neonates shortness of breath, weak body condition, yellowish skin. So that more effective service efforts need to be made, namely by providing comprehensive midwifery care where this care is expected to be able to detect early complications that occur from pregnancy to family planning with the hope that the mother is able to go through the process normally. The purpose of this study was to provide comprehensive care to Mrs